Students' Ethnic Background as a Factor in Their Involvement in Bullying - Kozmus, Andreja; Pšunder, Mateja (Revija za elementarno izobraževanje, 2019)
The multicultural character of EU countries has been steadily growing, and consequently, school classes are becoming increasingly ethnically diverse. Research performed worldwide on ethnic bullying in schools has yielded inconsistent results. The present empirical study investigated differences between groups regarding ethnicity and bullying among 782 students from grade 6 and grade 8 of Slovenian primary schools; among them, 140 were 1st- or 2nd- generation immigrants. The results showed that, compared to Slovenian boys, immigrant boys reported more often having been involved in bullying as observers, and 6th- grade immigrant students perceived themselves more often in the roles of observer and victim.